Embedding Cybersecurity into Smart Enterprise Systems: An Applied DevSecOps and Automation Approach - Talakola, Swetha (International Journal of AI, BigData, Computational and Management Studies, 2026)
Smart enterprise systems enabled by cloud-native platforms, artificial intelligence, data-driven automation, and continuous delivery models form the backbone of modern digital transformation initiatives. These systems allow organizations to achieve unprecedented levels of scalability, operational efficiency, and real-time responsiveness. However, their highly distributed, automated, and intelligent nature significantly expands the enterprise attack surface, exposing organizations to complex and fast-evolving cyber threats that traditional, perimeter-centric security approaches can no longer adequately address. Automated, AI-driven enterprises face distinct cybersecurity challenges, including increased exposure through APIs and microservices, configuration drift in infrastructure-as-code environments, supply chain vulnerabilities within CI/CD pipelines, and emerging risks related to AI model manipulation and data poisoning. The speed and autonomy of modern systems often outpace manual security controls, creating gaps in visibility, governance, and incident response. As a result, cybersecurity must transition from a reactive, compliance-driven function to an embedded, continuous capability within enterprise system lifecycles. This paper positions DevSecOps and security automation as foundational mechanisms for embedding cybersecurity into smart enterprise systems. By integrating security practices directly into development, deployment, and operational workflows, DevSecOps enables continuous risk assessment through automated testing, policy-as-code enforcement, and real-time monitoring. Security automation further enhances this approach by enabling scalable vulnerability detection, intelligent alerting, and rapid remediation without compromising delivery velocity. The study adopts an applied methodology that combines enterprise architecture analysis, DevSecOps workflow modeling, and the evaluation of automation use cases across CI/CD pipelines, cloud infrastructure, and runtime environments. Key findings indicate that organizations adopting embedded security through DevSecOps achieve measurable improvements in security posture, reduced mean time to detect and remediate threats, and stronger governance across hybrid and multi-cloud ecosystems. The paper contributes a practical, automation-driven framework to guide enterprises in aligning cybersecurity with intelligent system design, operational agility, and long-term resilience.